A homoafetividade na publicidade : um estudo de recepção - Mendonça, Flávio Costa de (2018)
This paper proposes a reception research about advertisements that approach homoaffective content in their campaigns, especially ones broadcasted on television, and its role in identity construction and in fighting homophobia. According to the Cultural Studies approach, mainly the latin-american theoretical-methodological work of Jesús Martín-Barbero. This research aims to verify the perception of young audiences about advertisements that features homosexual content, for that reason we did a theoretical survey about the way in which those individuals are represented in Brazilian cinema, soap operas and advertisements. A qualitative study of reception was carried with heterosexuals and homosexuals of different levels of education, of different social classes, between 18 and 24 years old living in the city of Aracaju, Sergipe. The techniques used to collect the data were a questionnaire and a in-depth interview, with the questionnaire being the first part of the research and the interview the second one. This we verified how young people think about homosexuals represented in advertisements and in society. We found two main troublesome factors for the young people who do not agree with the presence of gay couples in advertising pieces, they are religion and sexism.